Research of employees’ motivational potential in the social management system - Лутай, Лариса Анатоліївна; Черкасов, Андрій Володимирович; Рудь, Юлія Миколаївна (Technology audit and production reserves, 2015)
The process of motivational potential of the enterprise in the social management system is discussed in the article. The main aim of the study is to develop structure and relationship elements that create the concept of employees’ motivation and justification of its implementation. The elements that create the concept of employees’ motivation are discussed. Principles that facilitate the practical implementation of this concept are: consistency, effectiveness and objectivity. The presented concept allows to identify internal and external factors of influence on behavior and needs of employee, establish factors that inhibit the development of employees’ motivational potential to find ways to neutralize them; provide development of employees’ motivational potential by establishing optimal ratio between wages and productivity of employees. The method and algorithm designed to select the integrated management tools enhance the motivation of the organization on employees. The research results can be applied to the heads of commercial enterprises and scientists studying the motivational potential in the system of employees’ social management.